Bicentenaire des pratiques lexicales du bamanankan : Jean Dard 1825 – Dukure 2021 - Issiaka, Ballo (Language Policy in Africa, 2026)
While the french lexicography began with the publication of the first french dictionary, "Le Thésaurus," by Étienne Robert in 1531 (Gaudin 2000: 20), the publication of the French-Wolof-Bambara dictionary in 1825 by Jean Dard marked the beginning of the lexicography records in Bamanankan (Ballo 2024: 229). Two centuries have passed since this latter date. And two centuries of practice deserve to be celebrated, especially a practice carried out in a language falsely considered unwritten in the public mind. Thus, the present work recounts the major milestones in the general and specialized lexicography of Bamanankan. It presents both the history of the key figures involved and the history of the language's transcription, while also incorporating commentary, analysis, and discussion.